Stock Market Volatility during COVID-19 Pandemic - Anum Zahra; Malik Ghadeer Ul Hassan (ADI Publisher, 2021)
The study investigates the response of the stock market to the coronavirus pandemic. The economic consequences of the coronavirus (COVID-19) for the stock market are considerable for a developing country, like Pakistan, which was amongst the list of fifteen countries with the highest number of coronavirus cases in May 2020. The present study is aimed at finding the effect of an increase in the number of confirmed cases of coronavirus on the stock returns in the Pakistan stock market. Additionally, the study investigates the effect of an increase in the number of deaths on stock returns. The results show that an increase in the number of confirmed cases has a significant negative effect on the stock returns. While the increase in the number of deaths does not have a significant effect on the stock returns. The results are in line with the results of Ashraf (2020). The findings are important for the policymakers in formulating policies to safeguard the investors in the stock market during this uncertain time.